Comparative analysis of Ukrainian and international educational projects - Bohun, Valeriya; Onyshkevych, Oleksandra (Lviv Polytechnic Publishing House, 2016)
The cause of the problem is that under conditions of globalization the education is a highly productive form of the capital investment likewise the important social guarantee.
Keywords: Ukrainian projects; international projects; education